Age and growth of the deep water mud shrimp Solenocera melantho (De Man, 1907) off Visakhapatnam coast, India - Ganesh, P. R. C.; Chakravarty, Myla. S. (Indian Journal of Fisheries, 2016)
Age and growth of the deep water mud shrimp Solenocera melantho (De Man, 1907) was estimated using von Bertalanffy growth model employing modal progression analysis, Ford-Walford method for L∞ and K and t0 by Gulland’s method as well as ELEFAN I (FiSAT II software version 1.2.2) method. The growth parameters estimated by the former method were: L∞= 107.9 mm, K = 2.61 y-1, t0 = 0.1344, φ’ = 4.4825 for males and L∞ = 116.4 mm, K = 3.69 y-1, t0 = 0.1346, φ’ = 4.6997 for females and by the latter method were : L∞ = 106.1 mm, K = 2.17 y-1, t0 = -0.05, φ’ = 4.3879 for males and L∞ = 116.8 mm, K = 2.1 y-1, t0 = -0.05, φ’ = 4.4571 for females. The longevity estimated for both males and females of S. melantho was about 36 months. The females were observed to grow faster than the males.